EXPLORING THE USE OF DRAMA WAYANG FOR ESP SPEAKING ACTIVITIES - Dwi Wahyuningtyas; Adelia Savitri (University of Muhammadiyah Malang, 2022)
Drama is among English teaching and learning activities that can improve students' communication and speaking skills. However, only a few studies documented the integration between local culture and drama for English teaching and learning activities. This study aims at exploring the use of drama wayang in the English for Specific Purposes Speaking activities. A descriptive qualitative study was employed as the study design, with observation, documentation, and questionnaire as methods of data collection. The subjects of this study were first-semester university students from the Indonesian Language and Literature Department. Findings showed that students were enthusiastic about performing drama wayang and could perform it well. Furthermore, drama wayang can be integrated into English teaching and learning activities to improve activity variety and attract students’ interest in learning speaking. This study also implies that drama wayang can be developed into an ESP teaching method combined with Indonesia's local culture and serves as an innovative and contextual ESP teaching method.